Misleading information and investors. Back to the localisation of the financial damage - Sánchez Fernández, Sara (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
The pivotal element of capital markets regulation is disclosure. Where misleading information is disseminated, investors may suffer a pure economic loss, which is immaterial and, thus, difficult to locate. This paper covers the dynamics between information, price and damage in capital markets as the fundamental element to correctly locate financial loss in cross-border scenarios. On this basis, I analyse the CJEU case law on the interpretation of art. 7.2 Brussels I bis Regulation, in particular the latest judgment VEB, which apparently turns to a market-oriented location of the damage. Lastly, I discuss whether the conclusions may be extrapolated to the determination of the law applicable under art. 4.1 of Rome II Regulation.
Keywords: financial damage; capital markets; misleading information; international jurisdiction; law applicable